Local electronic structure of Fe2+ impurities in MgO thin films: temperature-dependent soft x-ray absorption spectroscopy study - Haupricht, Tim Jakobus Thomas; Haverkort, Maurits W. (Arxiv, 2010)
We report on the local electronic structure of Fe impurities in MgO thin films. Using soft x-ray absorption spectroscopy (XAS) we verified that the Fe impurities are all in the 2+ valence state. The fine details in the line shape of the Fe $L_{2,3}$ edges provide direct evidence for the presence of a dynamical Jahn-Teller distortion. We are able to determine the magnitude of the effective $D_{4h}$ crystal field energies. We also observed a strong temperature dependence in the spectra which we can attribute to the thermal population of low-lying excited states that are present due to the spin-orbit coupling in the Fe 3d. Using this Fe$^{2+}$ impurity system as an example, we show that an accurate measurement of the orbital moment in Fe$_3$O$_4$ will provide a direct estimate for the effective local low-symmetry crystal fields on the Fe$^{2+}$ sites, important for the theoretical modeling of the formation of orbital ordering.
Die Ziffer 2 sowie das +Zeichen im Titel sind hochgestellt
Gesehen am 27.11.2017